2021
DOI: 10.1039/d1ra06808c
|View full text |Cite
|
Sign up to set email alerts
|

Al-doped α-MnO2 coated by lignin for high-performance rechargeable aqueous zinc-ion batteries

Abstract: Al3+ doping combined with lignin coating improves the structural stability and electrochemical performance of the modified α-MnO2, L + Al@α-MnO2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 53 publications
(64 reference statements)
0
18
0
Order By: Relevance
“…Interestingly, Al-doped MnO 2 exhibited a sea urchin-like morphology with a size of 4.5-5.0 µm and an enlarged interlayer spacing (0.24 nm vs. 0.29 nm). Xiong et al reported that Al-doped α-MnO 2 coated with lignin was formed through a hydrothermal reaction involving KMnO 4 , NH 4 F, Al 2 (SO 4 ) 3 , and lignosulfonate at 200 • C, as illustrated in Figure 2a [44].…”
Section: Hydrothermal Methodsmentioning
confidence: 99%
“…Interestingly, Al-doped MnO 2 exhibited a sea urchin-like morphology with a size of 4.5-5.0 µm and an enlarged interlayer spacing (0.24 nm vs. 0.29 nm). Xiong et al reported that Al-doped α-MnO 2 coated with lignin was formed through a hydrothermal reaction involving KMnO 4 , NH 4 F, Al 2 (SO 4 ) 3 , and lignosulfonate at 200 • C, as illustrated in Figure 2a [44].…”
Section: Hydrothermal Methodsmentioning
confidence: 99%
“…The use of lignin-coated PEDOT in LIB displayed the highest specific capacity in the first cycle, but a better rate capability was confirmed in NIB. Lignin was also used in a Zn-ion battery (ZIB) [108][109][110]. ZIB has attracted attention because of its non-toxicity, high safety, high theoretical capacity of zinc (820 mAh g −1 ), and outstanding rate capability [111,112].…”
Section: Lignin-based Cathodesmentioning
confidence: 99%
“…However, ZIB has the limitation of the dissolution of transition metal from the cathode (i.e., Mn 2+ ) and forming of zinc hydroxide sulfate (ZHS), which causes a loss of capacity [113]. To suppress them, Lignin-coated a-MnO 2 nanorods and nanowires with Al 3+ dopant were synthesized with NH 4 F, Al 2 (SO 4 ) 3 , KMnO 4 , and sodium lignosulfonate using a hydrothermal method (Figure 10a) [110]. The MnO 2 with lignin shows 1D nanorods providing large reaction sites (Figure 10b).…”
Section: Lignin-based Cathodesmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 1D , the MZHCF (MZHCF-7) with Mn content of 7% retained 94% of the initial capacity (far more than 17% of ZnHCF) after 500 cycles at 0.25 Ag −1 , displaying a significant synergistic optimization effect. In addition, the gap doping of heteroatoms (especially metals with similar ion radius) has been proved to effectively stabilize the phase transition structure and inhibit the dissolution of materials, which contributes to improving the reversibility of cathodic electrochemical reaction ( Xu et al, 2021a ; Chen et al, 2021 ). Moreover, Wang et al obtained multivalent cobalt (Co 2+ , Co 3+ )-doped Mn 3 O 4 nanosheets (Co-Mn 3 O 4 /CNA) based on carbon nanosheets array by electrodeposition on the basis of Co-MOF precursors prepared in water bath and annealing ( Ji et al, 2021 ).…”
Section: Stability Optimizations For Cathode Materialsmentioning
confidence: 99%